2023
DOI: 10.1002/joom.1279
|View full text |Cite
|
Sign up to set email alerts
|

Friend or foe? The impact of refurbished products in markets with network effects and standards competition

Yilong (Eric) Zheng,
Qi Wang,
Chang Hee Park

Abstract: The practice of offering refurbished products has become increasingly prevalent, yet limited research has studied the potential consequences of this emerging product strategy on the market performance of the corresponding brand‐new products. This study addresses this gap by examining the impact of refurbished products in markets characterized by network effects and standards competition, while considering the developmental stage of the technology standard employed by the products. Introducing refurbished produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…For example, Guide and Li (2010) have shown that the sale price of new products in controlled auctions is not impacted by the presence of remanufactured product alternatives. In this special issue, Zheng et al (2024) examine markets for consumer electronics where remanufactured products are introduced. They discuss how this impacts consumer purchase intention and the sales of brand‐new products.…”
Section: Articles In This Issuementioning
confidence: 99%
“…For example, Guide and Li (2010) have shown that the sale price of new products in controlled auctions is not impacted by the presence of remanufactured product alternatives. In this special issue, Zheng et al (2024) examine markets for consumer electronics where remanufactured products are introduced. They discuss how this impacts consumer purchase intention and the sales of brand‐new products.…”
Section: Articles In This Issuementioning
confidence: 99%